Raman spectroscopic identification of Mycobacterium tuberculosis. Issue 5 (7th October 2016) - Stöckel, Stephan; Meisel, Susann; Lorenz, Björn; Kloß, Sandra; Henk, Sandra; Dees, Stefan; Richter, Elvira; Andres, Sönke; Merker, Matthias; Labugger, Ines; Rösch, Petra; Popp, Jürgen
Abstract : In this study, Raman microspectroscopy has been utilized to identify mycobacteria to the species level. Because of the slow growth of mycobacteria, the per se cultivation‐independent Raman microspectroscopy emerges as a perfect tool for a rapid on‐the‐spot mycobacterial diagnostic test. Special focus was laid upon the identification of Mycobacterium tuberculosis complex (MTC) strains, as the main causative agent of pulmonary tuberculosis worldwide, and the differentiation between pathogenic and commensal nontuberculous mycobacteria (NTM). Overall the proposed model considers 26 different mycobacteria species as well as antibiotic susceptible and resistant strains. More than 8800 Raman spectra of single bacterial cells constituted a spectral library, which was the foundation for a two‐level classification system including three support vector machines. Our model allowed the discrimination of MTC samples in an independent validation dataset with an accuracy of 94% and could serve as a basis to further improve Raman microscopy as a first‐line diagnostic point‐of‐care tool for the confirmation of tuberculosis disease. Abstract : Tuberculosis has been a scourge of humankind from time immemorial and is still one of the world's most dangerous diseases. Thus, the per se cultivation‐independent Raman microspectroscopy emerges as a perfect tool for a rapid on‐the‐spot mycobacterial diagnostic test. For the first time, it could be shown that a definite identification of mycobacterial species is possible by using Raman microspectroscopy on single bacterial cells in combination with elaborated statistical methods.